Potato Market Participation and Its Extents Evidence from Southwest Ethiopia: A Double Hurdle Approach - Abadega, Abduselam Faris (Universitas Muhammadiyah Yogyakarta, 2021)
Potato is an important commodity for livelihood in many parts of Ethiopia. Potato producers in Ethiopia face sophisticated marketing challenges, including inadequate access to market and low amount of marketed surpluses due to subsistence-oriented production of potato. The study aimed to identify factors that determine the market participation and its extents. About 136 potato producers were selected randomly from peasant association found in Dedo Districts of Ethiopia. Quantitative and qualitative data were collected from primary sources. Descriptive and econometric methods of data analysis were used to analyze data from the survey. A double hurdle model was applied to investigate factors affecting market participation and its extents. Results of descriptive statistics revealed that out of the total sample producer, 87.5 % of sample household has participated in the potato market. Age, sex, education, land size allocated for potato, and non-farm income were significantly influencing potato market participation. Age, sex, education (years of schooling), non-farm income, active labor and land allocated for potato influenced smallholder farmers level of market participation.